Changing Landscapes in Urban British Churchyards - Thornbush, Sylvia E. (Bentham Science Publishers, 2020)
This interdisciplinary reference work presents a linked consideration, to the reader, of physical-cultural (physicocultural) representations of headstones located in urban churchyards in England and Scotland. The geomorphology of landscapes relevant to these locations is explained with the help of detailed case studies from Oxford and Edinburgh. The integrated physicocultural approach addresses the conservation of the archaeological record and presents a cross-temporal perspective of landscape change - of the headstones as landforms in their landscape (as part of deathscapes). The physical rec.